Weak cosmic censorship conjecture in the pure Lovelock gravity. Issue 10 (1st October 2022) - Shaymatov, Sanjar; Dadhich, Naresh
Abstract: It is well known that a rotating black hole in four dimension could be overspun by linear order test particle accretion which however always gets overturned when non-linear perturbations are included. It turns out that in the Einstein gravity, repulsion due to rotation dominates over attraction due to mass in dimensions, D > 5, and consequently black hole cannot be overspun even for linear order accretion. For the pure Lovelock rotating black hole, this dimensional threshold is D > 4 DN + 1 where N is degree of single N th order term in the Lovelock polynomial in the action. Thus the pure Lovelock rotating black holes always obey the weak cosmic censorship conjecture (WCCC) in all dimensions greater than 4 N + 1. Since overall gravity being repulsive beyond this dimensional threshold, how is rotating black hole then formed there?